2018
DOI: 10.3390/agronomy8080153
|View full text |Cite
|
Sign up to set email alerts
|

Diallel Analysis for Morphological and Biochemical Traits in Tomato Cultivated under the Influence of Tomato Leaf Curl Virus

Abstract: Eloquent information about the genetic basis of inheritance is important for any breeding program. Therefore, a diallel study was conducted under the influence of tomato leaf curl virus (TLCV) disease, using the eleven advanced lines of tomato. Firstly, information regarding percent disease index (PDI) was determined via artificial screening with viruliferous whiteflies. Later, these lines were crossed in a half diallel mating design to produce fifty-five one-way hybrids. These hybrids and parental genotypes w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 53 publications
3
35
0
Order By: Relevance
“…The positive and negative heterosis was determined for ten characters. Heterosis over mid-parent has also been reported for fruit traits and yield components in chilli peppers, as well as in other members of the Solanaceae [15,17,30].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The positive and negative heterosis was determined for ten characters. Heterosis over mid-parent has also been reported for fruit traits and yield components in chilli peppers, as well as in other members of the Solanaceae [15,17,30].…”
Section: Discussionmentioning
confidence: 79%
“…Mean squares owing to parents, hybrids and parents versus hybrids were highly significant for all traits (Table 1). Similarly, the pooled analysis of variance over two seasons for morphological (15) and fruit biochemical (5) traits showed that mean squares due to general combining ability (GCA) and specific combining ability (SCA) were highly significant for all studied traits (p ≤ 0.01) ( Table 2). The results also indicate the involvement of both additive and non-additive genetic variance in governing the expression of the studied traits.…”
Section: Analysis Of Variance For the Experimental Designmentioning
confidence: 90%
See 1 more Smart Citation
“…Earlier studies pointed out the effect of cytoplasm sources on different traits and it was concluded that the cytoplasmic genome affects qualitative and quantitative traits [4446]. SCA effects are more important for cross-pollinated plants, whereas CGA effects are more important for self-pollinated plants [47]. Being a cross-pollinated plant sunflower showed significantly higher SCA values than corresponding GCA values for most of the 12 descriptors.…”
Section: Discussionmentioning
confidence: 99%
“…Tomato crop has different types of male sterility identified, but presently commercial hybrid seed production in tomato and brinjal possible with manual emasculation and hand pollination and it is economically viable and dominates in the seed industry. Though, the availability of different sterility methods can be used to avoid selfing and optimise crossing resulted in reducing the cost of hybrid seed production [45].…”
Section: Advances In the Understanding Of Molecular Mechanisms Underlmentioning
confidence: 99%